Social media content analytics: Study on business to consumer (B2C) fan-pages. - Kumaran, S. (Kalaignaan Publications, 2017)
One of the supreme way ofdirectly connecting with consumers via Social Networking Sites (SNS) is to generate a brand page in Facebook (called fan page) containing products information and publish regular postings on these pages. Customers will reply differently to these postings. In defming the effectiveness of social networking sites, marketers are measuring metrics to calculate the engagement rate (e.g. number of comments/share and likings in fan pages). The study applied Pseudo-theories and analyzed a total 3543 brand posts from 19 of the most popular B2C (Business to Consumer) fan pages of Malaysia. 12 months' worth of data (From September 2015- August 2016) were collected for analyses, which were available online from the Brand's fan pages. The Fan-page content was analyzed using Cross Section Regression ofthe EVIEWS 9 software for its impact on multiple contents upon user's engagement actions. The study explored the content features (content quality, content valence and content volume) of S-O-R (Stimulus -Organism- Response) model and identify their impact on user's engagement actions (Like, comments and shares). The findings of the study will direct e-marketers to apprise informational analyses upon the effectiveness of the posted contents' features.